Factors Affecting Spermatozoa Motility Analysis using CASA - Dian Ratnawati; N Isnaini; T Susilawati (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Motility is a very important parameter to determine the quality of semen. Spermatozoa motility assessment can be done manually (subjectively) or with CASA. The superiority of motility assessment using CASA compared to manually is more objective, accurate, fast, efficient and able to provide detailed motility of spermatozoa. However, in implementation, assessments with CASA produce varied data. So far, there has not been a spermatozoa motility standard with CASA, except by minimizing variations in the factors that influence the results of analysis with CASA. The purpose of this paper is to describe factors that affecting spermatozoa motility analysis using CASA to reach optimal motility analysis. Some influencing factors include: CASA settings, semen diluent, spermatozoa concentration, chamber, analyst, sample preparation and analysis time. Recommendation standard motility assessments using CASA include: experienced and consistent analysts, sample preparation properly (mixing, pipeting and sampling), spermatozoa concentration of 20 million / ml, consistent in chamber type (conditioned 37°C), semen diluents and CASA settings (frame rate of 60 Hz and frame per field 30) and fast implementation of analysis (